2021
DOI: 10.1038/s42256-020-00285-9
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning framework for high-throughput mechanism-driven phenotype compound screening and its application to COVID-19 drug repurposing

Abstract: Phenotype-based compound screening has advantages over target-based drug discovery, but is unscalable and lacks understanding of mechanism. Chemical-induced gene expression profile provides a mechanistic signature of phenotypic response. However, the use of such data is limited by their sparseness, unreliability, and relatively low throughput. Few methods can perform phenotype-based de novo chemical compound screening. Here, we propose a mechanism-driven neural network-based method DeepC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 52 publications
0
99
0
Order By: Relevance
“…The copyright holder for this preprint this version posted August 10, 2021. ; https://doi.org/10.1101/2021.08.09.455708 doi: bioRxiv preprint 22 novel chemical representation module in DeepCE, our model can satisfy the prediction of chemical phenomics under the circumstance of both novel cells/patients and novel drugs 35 . We demonstrated that the predicted chemical transcriptomics were informative to downstream applications.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted August 10, 2021. ; https://doi.org/10.1101/2021.08.09.455708 doi: bioRxiv preprint 22 novel chemical representation module in DeepCE, our model can satisfy the prediction of chemical phenomics under the circumstance of both novel cells/patients and novel drugs 35 . We demonstrated that the predicted chemical transcriptomics were informative to downstream applications.…”
Section: Discussionmentioning
confidence: 94%
“…We augmented our data using a modified procedure described elsewhere 35 . We performed the data augmentation procedure multiple times which is inspired by teacher-student model.…”
Section: Teacher-student Model For Data Augmentationmentioning
confidence: 99%
“…Pham et al proposed DeepCE, a deep learning algorithm to repurpose drug compounds. The author demonstrated the application of DeepCE to predict potential leads for COVID-19 treatment [ 146 ]. In another study, an ML model was built to predict new indications for existing drugs and herbal compounds based on 1330 positive drug-disease associations though it was not directed against COVID-19 [ 147 ].…”
Section: Application Of Ai In Drug Discoverymentioning
confidence: 99%
“…Remdesivir is the only antiviral drug approved or authorized for emergency use from several international drug agencies, but not by the World Health Organization (WHO), to treat hospitalized COVID-19 patients ( https://www.covid19treatmentguidelines.nih.gov/antiviral-therapy/remdesivir/ ; https://www.ema.europa.eu/en/news/ema-provides-recommendations-compassionate-use-remdesivir-covid-19 ; https://www.tga.gov.au/media-release/australias-first-covid-treatment-approved ; https://www.who.int/news-room/feature-stories/detail/who-recommends-against-the-use-of-remdesivir-in-covid-19-patients ). While the potential clinical efficacy of molecules emerging from high throughput screens is explored ( Pham et al, 2021 ), the use of dexamethasone in patients with severe disease has been established with the Randomised Evaluation of COVID-19 Therapy (RECOVERY) trial ( Horby et al, 2021 ). More controversial is the use of glucocorticoids in patients who are not on supplemental oxygen in the Intensive Care Unit and the use of nonsteroidal anti-inflammatory drugs (NSAID)s to quell the immune response at any stage of the disease.…”
Section: Introductionmentioning
confidence: 99%